INFLUENCE OF RIFT ZONES AND THERMOKARST LAKES ON THE FORMATION OF SUBAQUEOUS PERMAFROST AND THE STABILITY ZONE OF METHANE HYDRATES OF THE LAPTEV SEA SHELF IN THE PLEISTOCENE - V. V. Malakhova; A. V. Eliseev (Лëд и снег, 2018)
This paper presents results of the analysis of the influence of talik zones associated with thermokarst lakes and processes in rift zones on the dynamics of subaqueous permafrost and zones of stability of methane hydrates for conditions of theLaptev Seashelf. The model of thermophysical processes in the bottom sediments together with the scenario of climate change on the Arctic shelf for the last 400 thousand years (kyr) were used. Typical value of geothermal heat flux for the most part of the shelf and for the shallow shelf (with the present-day depth of ≤50 m) is estimated as 60 mW/m2. It is shown that with this value the duration of the interglacials and the corresponding ocean transgression periods is not sufficient for the complete degradation of permafrost and destruction of the gas hydrates. For a deeper shelf, however, the complete disappearance of the stability zone of the methane hydrates is possible during the interglacial periods. In the areas of oceanic faults (rifts), higher values of the deep heat flux increase rates of degradation of the underwater permafrost rocks in the interglacial periods as compared with the condition when the heat flux is 60 mW/m2. Intensification of degradation of the subsea permafrost is manifested in areas where thermokarst lakes arise, but here it is associated with the temperature rise at the upper boundary of the bottom sediments. The presence of the rift zones and/or the thermokarst lakes promotes decreasing of the presentday thickness of the permafrost, and simultaneous impact of these two factors can lead to a through thawing of the shelf in the interglacials (including Holocene).